The Effectiveness of Brain Mapping Method In Students’ Reading Comprehension by Using Blogger Based in Merdeka Curriculum - Rosiana, Caltira; Rina Puji Utami (Cakrawala: Jurnal Pendidikan, 2023)
Most of the students got low scores in reading and understanding the material in online classes, this situation should be attention to Merdeka Curriculum. Most of the students lack interest in learning reading in an online class, because the learning methods in reading did not attract students, so the students had difficulty in answering explicit and implicit questions in reading comprehension. The purpose of this research is to determine the significant differences before and after using the brain mapping method in students' reading comprehension. This research designed as quantitative research that used one group pre-test and post-test design. sample amounted to 35 students. Collecting data used documentation and reading comprehension tests which were analyzed using Paired T-test with the help of SPSS 18 for Windows and N-Gain using Microsoft Excel. The post-test average learning outcome (77,29) was greater than the pretest (69.00). The results of the paired t-test showed the significance value (2-tailed) was 0.000 means there was significant effectiveness before and after using the Brain Mapping method toward Blogger as the online media for learning reading. The results of N-Gain showed the students’ learning outcomes improved from 35 students, 21 (60%) students got improvement in the medium category and 14 (40%) students got improvement in the low category. Brain mapping method combined with rewards and interesting materials can improve student achievement where students are more active and enthusiastic in the online teaching and learning process.,